DESARROLLO DE UN SISTEMA AUTOMATIZADO PARA LA DISTRIBUCIÓN DEL SERVICIO DE AGUA POTABLE EN UNA MUNICIPALIDAD - Hinostroza Alviar, Lesly Katheryne (2022)
For the residents of the Salas district, having access to clean water 24 hours a day, seven days a week is an unattainable dream, which motivates this study to find out the reasons why providing clean water in the district is difficult, with the objective of improving the management of the clean water service in charge of the Municipality of Salas, through this study to implement a SCADA system to improve water management with the favorable opinion of the citizen. The development of the project is divided into seven chapters. The first chapter is a study of the analysis of the organization, which explains the problem that exists. The second chapter discusses the theoretical framework of the company, as well as the analysis of the project and its management. The third chapter is dedicated to the initiation and planning of the project, from conception to its stakeholders. The concepts that must be considered when applying the design are presented. The fourth chapter develops the execution, supervision and control of the project creating various formats such as schedules, cost tables and change requests, among others. The fifth chapter concluded the project by accepting the sponsor of the results, thus approving the project. The sixth chapter evaluated the expected results of the project implementation to quantify and conclude the effectiveness of the project. The final chapter develops the conclusions and recommendations of the project team. vi Key Words: Scada System, Hall Municipality, Water Management